Anchored in Place Rethinking the University and Development in South Africa - Bank, Leslie; Cloete, Nico; van Schalkwyk, Francois (African Minds, 2018)
"Tensions in South African universities have traditionally centred around equity (particularly access and affordability), historical legacies (such as apartheid and colonialism), and the shape and structure of the higher education system. What has not received sufficient attention, is the contribution of the university to place-based development. This volume is the first in South Africa to engage seriously with the place-based developmental role of universities. In the international literature and policy there has been an increasing integration of the university with place-based development, especially in cities. This volume weighs in on the debate by drawing attention to the place-based roles and agency of South African universities in their local towns and cities. It acknowledges that universities were given specific development roles in regions, homelands and towns under apartheid, and comments on why sub-national, place-based development has not been a key theme in post-apartheid, higher education planning. Given the developmental crisis in the country, universities could be expected to play a more constructive and meaningful role in the development of their own precincts, cities and regions. But what should that role be? Is there evidence that this is already occurring in South Africa, despite the lack of a national policy framework? What plans and programmes are in place, and what is needed to expand the development agency of universities at the local level? Who and what might be involved? Where should the focus lie, and who might benefit most, and why? Is there a need perhaps to approach the challenges of college towns, secondary cities and metropolitan centers differently?"